Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."-- Provided by publisher.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé